Emergent constraint on oxygenation of the upper South Eastern Pacific oxygen minimum zone in the twenty-first century - Almendra, Ivan (2024)
As a consequence of on-going global warming, the ocean is losing oxygen, which has implications not only in terms of marine resources management and food supply but also in terms of the potentially important feedback on the global carbon cycle and climate. Of particular scrutiny are the extended zones of already low levels of oxygen called the oxygen minimum zones (OMZs) embedded in the subsurface waters of the productive Eastern Boundary Upwelling Systems (EBUS). These OMZs are currently diversely simulated by state-of-the-art Earth System Models (ESM) hampering a reliable projection of ocean deoxygenation on marine ecosystem services in these regions. Here we focus on the most emblematic EBUS OMZs of the planet, that of the South Eastern Pacific (SEP), which is under the direct influence of the El Niño Southern Oscillation (ENSO), the main climate mode on interannual timescales at global scale. We show that, despite the low consensus among ESM long-term projections of oxygen levels, the sensitivity of the depth of the upper margin (oxycline) of the SEP OMZ to El Niño events in an ensemble of ESMs can be used as a predictor of its long-term trend, which establishes an emergent constraint for the SEP OMZ. Because the oxycline along the coast of Peru and Chile deepens during El Niño events, the upper bound of the SEP OMZ is thus likely to deepen in the future climate, therefore oxygenating the SEP OMZ. This has implications not only for understanding the nitrogen and carbon cycles at global scale but also for designing adaptation strategies for regional upper-ocean ecosystem services.